Prevalence, Predictors and Point of View Toward Self-Medication Among Residents of Riyadh, Saudi Arabia: A Cross-Sectional Study - Mannasaheb, Basheerahmed Abdulaziz; Alajlan, Sarah Abdulrahman; Alshahrani, Jaber Abdullah; Othman, Noordin; Alolayan, Sultan Othman; Alamrah, Mohammed Saleh; Asdaq, Syed Mohammed Basheeruddin; Al-Qahtani, Awad Mohammed; Shaikh, Ibrahim Ahmed; Alasmary, Mohammed Yahia (Frontiers in Public Health, 2022)
Irrational Self-Medication (SM) practice leads to incorrect diagnosis and is a risk factor for disease exacerbation and serious health consequences. Hence Responsible SM is vital for better health outcomes. In the present community-based study we explored the SM practice during the last 3 months, frequency, outcome, medications used, reasons influencing SM, source of the drug, and information. Data were analyzed using SPSS; chi-square test was performed to indicate significance, Odds ratio, Pearson correlation, univariant and multivariant regression analysis were performed to find out factors and predictors of SM. A total of 611 residents completed the survey. SM was practiced by 52.9% of participants during the last 3 months, with a frequency of one to two times. Headache (64.8%), pain (35.4%), fever/flu (31.4%), cold & cough (21.9%) and dysmenorrhea (20.9%) were illnesses managed using pain killers (75.9%), multivitamins (25.5%), anti-pyretic (24.7%) and herbal medicines (18.5%). Minor illness (67.9%), earlier experience (33.9%) and shortness of time to attend healthcare facilities (18.8%) were the reasons for practicing SM. Distance to healthcare and routine physical activity have significantly influenced the SM practice. Residents stated that inappropriate SM would lead to negative outcomes, including drug side effects (70%), Interaction (34.2%), poor treatment outcome (32.6%) and return of symptoms (26.5%). Interestingly, two-thirds of participants (68.9%) have recommended SM in case of minor illnesses only, 85.3% of respondents have expressed their desire to learn more about appropriate SM, and 76.6% are willing to return their leftover or unused medications to drug take-back centers.